Regarding on The Novel Forms of the (3+1) - Dimensional Kadomstev-Petviashvili Equation - Bulut, Hasan; Demirdag, Betul; Baskonus, Had Mehmet (E D P Sciences, 2017)
This article, we have applied the Bernoulli Sub-Equation method to the (3+1)-Dimensional Kademstev-Petviashvili equation. We have obtained some new analytical solutions such as exponential function and rational solutions by using this technique. We have observed that two analytical solutions have been verified the (3+1)-Dimentional Kadomstev-Petviashvili equations by using Wolfram Mathematica 9. At the end of this manuscript, we submitted a conclusion in a comprehensive manner.
2nd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 20-22, 2017 -- Istanbul, TURKEY